(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article systematically analyzes the diet of pregnant women and its impact on fetal development based on scientific sources and statistical data. The literature was reviewed, and the relationships between micronutrients (iron, folate, iodine, and vitamin D), macronutrients, dietary diversity, maternal weight, and fetal outcomes (low birth weight, preterm birth, neurological development) were discussed. The article also provides recommendations for healthcare policy and practice.